Increased phagocytosis of Plasmodium falciparum-infected erythrocytes with haemoglobin E by peripheral blood monocytes - Ahnond Bunyaratvej (2018)
Erythrocytes from subjects with homozygous and heterozygous haemoglobin E (HbE) infected with Plasmodium falciparum in vitro were phagocytosed to a greater extent by normal human monocytes than infected erythrocytes from normal subjects. Susceptibility to phagocytosis was maximal when the parasites developed to trophozoite and schizont stages in both normal and patients' erythrocytes. The increased susceptibility of P. falciparum-infected HbE erythrocytes to phagocytosis by monocytes may play a role in protection against malaria. © 1986 S. Karger AG, Basel.